PRAKTEK RAMALAN DALAM PERSPEKTIF PASAL 545 AYAT (1) KITAB UNDANG-UNDANG HUKUM PIDANA - Mujib, Muhamad Abdul (Jurnal Hukum Magnum Opus, 2018)
The occult world in Indonesia has become an inseparable culture of the people, these occult experts are commonly called with shamans, paranormal, kiyai, ustadz etc., the average person is considered to have more supernatural abilities than others. In general, people in Indonesia strongly believe in things that are mystical/occult, especially Javanese society that until this modern period still hold firm beliefs of ancestral heritage tradition. The types of klenik in Java is very diverse to follow the tastes and understanding of society in general even a shaman claims himself as a multitalent who can resolve all kinds of problems ranging from mate affairs, fortune-predicting fortune, treatment, penglarisan, just stuff that smells Unbelievers, but the belief that thrives in this society is utilized by a handful of people to gain profits by claiming to have supranataural ability, some even claim to be able to bring Money unseen this becomes a phenomenon in the community and many believe it. As with the Predictive Predictions that say the ability to predict one's fate and fortune in the near or far future, the method used varies according to the dukun's belief. The question is whether or not it is just a form of fraud, then how does the law act in Indonesia in handling the phenomenon that has been in trust the community? Key word: culture, phenomena, magic/supranatural, fraud